Moisture-based green energy harvesting over 600 hours via photocatalysis-enhanced hydrovoltaic effect - Duan, Peng; Wang, Chenxing; Huang, Yinpeng; Fu, Chunqiao; Lu, Xulei; Zhang, Yong; Yao, Yuming; Chen, Lei; He, Qi-Chang; Qian, Linmao; Yang, Tingting (Nature communications, 2025)
Harvesting the energy from the interaction between hygroscopic materials and atmospheric water can generate green and clean energy. However, the ion diffusion process of moisture-induced dissociation leads to the disappearance of the ion concentration gradient gradually, and there is still a lack of moisture-based power generation devices with truly continuous operation, especially the duration of the current output still needs to be extended. Here, we propose a design for reconstructing the ion concentration gradient by coupling photocatalytic hydrogen evolution reaction with hydrovoltaic effect, to report a moisture-enabled electric generator (MEG) with continuous current output. We show that the introduction of the photocatalytic layer not only absorbs light energy to greatly increase the power generation of the MEG (500% power density enhancement), but more importantly, the photocatalytic hydrogen evolution process consumes the pre-stacked ions to restore the ion concentration gradient, allowing the MEG to continuously output current for more than 600 hours, which is 1 to 2 orders of magnitude higher than the great majority of existed MEGs in terms of the current output duration. This study designs a moisture-enabled electric generator (MEG) with a photocatalytic layer, achieving a 500% power density enhancement and continuous current output for over 600 hours, addressing the challenge of extended operation duration